Inertial relief technique based analysis of the three-wheeler E-vehicle chassis. (2022) - Waseem, Mohammad; Ahmad, Mumtaz; Parveen, Aasiya; Suhaib, Mohd
Abstract: In the current era, peoples are looking alternative solution in place of the conventional fuel powered vehicles. Electrical powered assisted vehicles are the appropriate solution to decarbonize the transportation sector. Three-wheeled "electric" vehicles that introduced in Indian cities for transport facility at the congested areas are getting exclusive attention. The frame of the three-wheeled "electric" vehicle is a primary element as it supports internal as well as external load. Static analysis of chassis can't be performed directly since the stiffness matrix becomes singular due to inflexible body movement of the three-wheeled frame due to unconstrained characteristics. In the present work, Inertia relief methodology is adopted to analyse the unconstrained chassis of the three-wheeled "electric" vehicle using FEM in the ANSYS® 15.0 workbench tool. SolidWorks® modelling environment is used to construct 3D chassis of the three-wheeled "electric" vehicle. Inertia relief analysis is performed to find out the directional deformation, equivalent von Mises stress, and force reaction for 2G vertical loading for existing and modified chassis of the three-wheeled vehicle respectively. Further, the inertia relief translational and rotational accelerations are computed to counterbalance the externally applied loads for existing and modified chassis under 2G vertical loading.